Optimization of Group Investigation (GI) Co-operative Learning Model to Improve Students' Creativity in Science Learning - Apriani, Apriani; Kormil Saputra; Chanakan Sojayapan (Classroom Experiences, 2024)
This study aims to determine the level of student creativity by using the group investigation (GI) type cooperative learning model in class V of 48 Ampenan State Elementary School (SDN). The type of research used is class action research. This research was conducted in class V of SDN 48 Ampenan in the 2022/2023 academic year. Based on the results and analysis in each cycle, it can be concluded that in applying the cooperative learning model of group investigation (GI) type can increase student creativity in class V SDN 48 Ampenan in the 2022/2023 lesson year in learning science with the results of cycle I and cycle II. From several aspects of cycle I assessment, individual completeness is 100, for learning completeness or classical completeness is 16% and the last for the percentage or average indicator is 55.5%. The assessment aspects of cycle II individual completeness value is 100, classical completeness or learning completeness is 100 and the last to calculate the percentage or average indicator is 76% the frequency category is creative. The difference in the increase in creativity results from cycle I and II is 20.5%.